2022
DOI: 10.7759/cureus.30465
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Community Levels of Knowledge About Developmental Dysplasia of the Hip, its Risk Factors, Treatment, and Complications in the Riyadh Region, Saudi Arabia

Abstract: BackgroundDevelopmental dysplasia of the hip (DDH) can involve an immature hip, acetabular dysplasia with or without subluxation, or dislocation of the femoral head. The prevalence of DDH in Saudi Arabia is 10.46 per 1000 live births, highlighting the importance of community knowledge of DDH risk factors and treatment to facilitate early diagnosis, treatment, and avoiding complications. AimOur goal is to assess community awareness of DDH and the knowledge of its risk factors, treatment, and complications among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
1
1
1
Order By: Relevance
“…In regards to the primary knowledge about DDH, according to the findings in current study, caregivers who have no primary knowledge about DDH represent the largest proportion than those with knowledge. This result agrees with (15).This study found that the majority had a low knowledge level regarding DDH. As for the family history, the study states that it is not found in most of the sample study (62%); this finding comes along with the study of ( 16) which found that most of participant are negative in the results of family history in (77.8%).…”
Section: Discussionsupporting
confidence: 90%
“…In regards to the primary knowledge about DDH, according to the findings in current study, caregivers who have no primary knowledge about DDH represent the largest proportion than those with knowledge. This result agrees with (15).This study found that the majority had a low knowledge level regarding DDH. As for the family history, the study states that it is not found in most of the sample study (62%); this finding comes along with the study of ( 16) which found that most of participant are negative in the results of family history in (77.8%).…”
Section: Discussionsupporting
confidence: 90%
“…This factor showed a correlation between our study and a previous study, which reported that respondents became aware of DDH because a family member was affected by it [10]. In comparison to another study conducted in 2022 in the Riyadh region, Saudi Arabia, which showed that 72.8% had a low knowledge level regarding DDH, our study's findings are consistent [13]. Around 48.9% had moderate awareness, and 37.8% had low awareness.…”
Section: Discussionsupporting
confidence: 87%
“…A Saudi study involving participants in Riyadh reported that the results about the awareness of DDH were suboptimal. Furthermore, the awareness level, in this study, was much lower among fathers than mothers [13].…”
Section: Discussioncontrasting
confidence: 62%
“…Diagrams and images were also provided to aid in understanding. These questions and answers were referenced from a previous questionnaire conducted in Saudi Arabia, Riyadh, and were reviewed by four pediatric orthopedic doctors [12]. The second section of the questionnaire contained 12 questions, and every right answer was granted 1 mark.…”
Section: Data Collection Toolmentioning
confidence: 99%